If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = 3y + 27 Reorder the terms: 12 = 27 + 3y Solving 12 = 27 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 12 + -3y = 27 + 3y + -3y Combine like terms: 3y + -3y = 0 12 + -3y = 27 + 0 12 + -3y = 27 Add '-12' to each side of the equation. 12 + -12 + -3y = 27 + -12 Combine like terms: 12 + -12 = 0 0 + -3y = 27 + -12 -3y = 27 + -12 Combine like terms: 27 + -12 = 15 -3y = 15 Divide each side by '-3'. y = -5 Simplifying y = -5
| y^2-y*5-14=0 | | x^2-5x=-3x+15 | | p(x)=x^3-5x^2-6x | | 3x-20=30 | | (6-x)+(4y-10)i=12-6i | | 28(3)=x | | 33+3x=34 | | 9x+2=8x-5 | | 29f-73=420 | | 52-18=x | | (5x-9)(7x+2)= | | 9x-4=5/8 | | 0=0.66x+1 | | 1.2-1.9x=0.5(x+3)-0.3(x+5) | | y=3x+68 | | 67(k+79)=313 | | -2x+11=8 | | 6x=-11x-3 | | f(x)=-0.02x^2+x+5.75 | | 7x-11=4x-2 | | 3x+1.5=4.6 | | d/dx((1000)(1.03^x)) | | 175(330-x)+90x=39560 | | 4x^2-y^2+4y-5=0 | | -30=-6g | | -2/3x-4 | | 10x+2=12x+4 | | x=11+4y(-2) | | 1-3(x+8)=-2x-18 | | lne^3x=22 | | (x+(8-3i))(x+(8+3i))=0 | | -5r-29=7(8-4r)+6r |